Existence And Position Of Paralegal In Legal Assistance And Provision Of Legal Aid In Indonesia - Adiputra, Muhammad Raafi; Sri Utari, Indah (Law Research Review Quarterly, 2025)
In a state governed by the rule of law that upholds the principles of equality before the law and access to justice , the provision of fair and equitable legal aid is a fundamental human right that must be guaranteed by the state. However, in practice, legal access disparities persist, particularly among the poor, vulnerable groups, and communities in remote areas. In response to the limited availability of lawyers and legal aid services, paralegals emerge as non-professional actors who perform non-litigation legal assistance roles. This study aims to analyze the legal legitimacy and existence of paralegals within Indonesia’s legal system. Using a normative juridical approach, supported by historical and conceptual analysis, the study finds that paralegals gain legal standing through Law No. 16 of 2011 and its derivative regulations. Nevertheless, their formal recognition remains limited, especially following Supreme Court Decision No. 22 P/HUM/2018, which restricts paralegals from participating in litigation processes. This limitation overlooks the significant role paralegals play in legal education, community advocacy, and grassroots legal empowerment. Therefore, policy reform and stronger legal recognition are urgently needed to enable paralegals to contribute more effectively to the realization of substantive justice and broader access to legal remedies.